PENGARUH FINANCIAL DISTRESS, RISIKO KUALITAS AUDIT, DAN OPPORTUNITIES TO MANIPULATE INCOME TERHADAP AUDITOR SWITCHING - Adelia Fildzah Nadhilah (CV. Doki Course and Training, 2023)
ABSTRACK This study aims to examine the effect of Financial Distress, Audit Quality Risk, and Opportunities to Manipulate Income with the control variable, namely Company Size on Auditor Switching before and during the Covid-19 pandemic. The data used in this study is secondary data with a population of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The sampling technique in this study used a purposive sampling technique and produced a total sample of 100 companies. The results showed that Audit Quality Risk and Opportunities to Manipulate Income had an effect on Auditor Switching while Financial Distress controlled by Firm Size had no effect on Auditor Switching. Keywords: Auditor Switching, Financial Distress, Audit Quality Risk, Opportunities to Manipulate Income, Company Size, Covid-19 Pandemic. ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh dari Financial Distress, Risiko Kualitas Audit, dan Opportunities to Manipulate Income dengan variabel kontrol yaitu Ukuran Perusahaan terhadap Auditor Switching pada sebelum dan pada masa pandemi covid-19. Data yang digunakan dalam penelitian ini adalah data sekunder dengan populasi perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2019-2020. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling dan menghasilkan jumlah sampel sebanyak 100 perusahaan. Hasil penelitian menunjukkan bahwa Risiko Kualitas Audit dan Opportunities to Manipulate Income berpengaruh terhadap Auditor Switching sedangkan Financial Distress dengan dikontrol Ukuran Perusahaan tidak memiliki pengaruh terhadap Auditor Switching.